Interventions for improving medication adherence in solid organ transplant recipients - Mellon, Lisa (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: This review aims to look at the benefits and harms of using interventions for improving adherence to immunosuppressant therapies in solid organ transplant recipients, including paediatric and adult heart, lung, kidney, liver and pancreas transplant recipients.